STRATEGIES OF ISLAMIC BOARDING SCHOOL TEACHERS OF ENGLISH TO DEVELOP STUDENTS’ MULTILINGUAL COMPETENCIES - Hajriah, Hajriah; Abduh, Amirullah; Korompot, Chairil Anwar (JTechLP: Journal of Technology in Language Pedagogy, 2023)
The purposes of this study were to find out 1) The strategies used by English teachers in Islamic boarding schools to develop students' multilingual competence. 2) The challenges faced by English teachers in Islamic boarding schools in developing students' multilingual competencies. 3) Facilities used by English teachers in Islamic boarding schools to develop students' multilingual competencies. This study is qualitative research that uses an exploratory descriptive qualitative method. The participants of this research are English teachers and students in MTS Hj. Haniah and MA Hj. Haniah. The instruments used in this research are interviews and observation. Interviews were conducted with two English teachers and eight students who had been selected using purposive sampling techniques. Observations were made inthe classroom during the learning process and also in the dormitory environment. The results of this study show that there are seven strategies used by English teachers in Islamic boarding schools, including visual, project-based learning, group-individual learning, peer tutoring, daily conversation, vocabulary list,and window-shopping strategies. The challenges faced by English teachers in boarding schools include the lack of English teachers, inadequate facilities, lack of student interest in learning, and students' difficulties in learning two languages at once. The facilities used by English teachers at the boarding school includeclassrooms, dormitories, a library, and a language laboratory.